Risk factors for death in Welsh infants with a congenital anomaly - Ho, P; Quigley, M; Tucker, D; Kurinczuk, J (BMJ Publishing Group, 2021)
Objectives To investigate risk factors associated with death of infants with a congenital anomaly in Wales, UK.